2012
DOI: 10.1248/cpb.60.790
|View full text |Cite
|
Sign up to set email alerts
|

Cuspidans A and B, Two New Stilbenoids from the Bark of <i>Gnetum cuspidatum</i>

Abstract: Cuspidan A (1), a new stilbene sestermer consisting of a resveratrol, an oxyresveratrol, and a 3,5-dihydroxyphenylmethanol constituent units and cuspidan B (2), a new tri-cyclic stilbene monomer were isolated from the bark of Gnetum cuspidatum. The structures and configurations of 1 and 2 were elucidated on the basis of 2D-NMR correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Thes tereochemical outcome of 25 indicated that ac ationic-triggered C8 epimerization might be involved during this cyclization. Thes pectra of 25 were identical in all respects to the data reported in the literatures, [3a, 30b,c] which represents af ormal total synthesis of 8-epi-Liphagal (26).…”
Section: Angewandte Chemiesupporting
confidence: 77%
See 1 more Smart Citation
“…Thes tereochemical outcome of 25 indicated that ac ationic-triggered C8 epimerization might be involved during this cyclization. Thes pectra of 25 were identical in all respects to the data reported in the literatures, [3a, 30b,c] which represents af ormal total synthesis of 8-epi-Liphagal (26).…”
Section: Angewandte Chemiesupporting
confidence: 77%
“…Through esterification with propargylic acid and palladium-catalyzed cyclization, [25] 2af could advance to anhydromarmesin (18)in39%yield. Global or partial demethylation of 4p gave the corresponding Cuspidan B( 19,H L-60 cell inhibitor) [26] and Stemofuran B (20,a nti-inflammatory activity) [27] in 93 %a nd 68 %y ield, respectively.A fter protecting group manipulation, 4q was transferred to Gnetucleistol C [28] (21)i n4 9% yield. Global demethylation of 6bcould afford Wittifuran E(22,pancreatic lipase inhibitor) [29] in 88 %yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…1 Conclusion Four known stilbenoids were successfully isolated and characterized from the methanol extract of the lianas of Gnetum cuspidatum Blume. These stilbenoids compounds include resveratrol (1), gnetucleistol C (2), gnetucleistol D (3) and gnemonol M (4). As previous study found that oligostilbenoids from Gnetum displayed diverse pharmacological properties, further detailed on its phytochemical investigation is worth to be explored.…”
Section: Resultsmentioning
confidence: 96%
“…Gnetum cuspidatum Blume is known throughout tropical Southeast Asia from Thailand, Vietnam, Cambodia, Malaysia, Sumatra, Java, and Borneo to the Maluku, Sulawesi and New Guinea. Previous study revealed the isolation of isorhapontigenin from the stem [3] and two new compounds recently report by Shimokawa et al [4] known as cuspidan A and cuspidan B from the bark of this plant.…”
Section: -2506mentioning
confidence: 99%
“…Through esterification with propargylic acid and palladium‐catalyzed cyclization, 2 af could advance to anhydromarmesin ( 18 ) in 39 % yield. Global or partial demethylation of 4 p gave the corresponding Cuspidan B ( 19 , HL‐60 cell inhibitor) and Stemofuran B ( 20 , anti‐inflammatory activity) in 93 % and 68 % yield, respectively. After protecting group manipulation, 4 q was transferred to Gnetucleistol C ( 21 ) in 49 % yield.…”
Section: Resultsmentioning
confidence: 99%